The colonial response to the development of disease in Ghana and Côte d’Ivoire (ca. 1900-1955): A comparative analysis of British and French colonial health policies - Arlinde C. E. Vrooman (PLoS ONE, 2025)
Using a newly constructed dataset of official morbidity figures based on colonial medical reports, this article studies the British and French colonial response to the development of fourteen selected diseases in colonial health care facilities in Ghana and Côte d’Ivoire from circa 1900–1955. Yaws and malaria are shown to have received colonial attention due to their relatively high incidence in the facilities, while other diseases were deemed important for reasons other than the number of cases treated (sleeping sickness, yellow fever, smallpox). Despite similar forces surrounding colonial decision-making (such as the expansion of the colonial health care networks, population growth and the development of Western medicine), the British and French colonial response developed differently for part of the selected diseases (including sleeping sickness, measles and dysentery). For five commonly prevalent diseases (leprosy, dysentery, measles, gonorrhoea and syphilis) in Ghana and Côte d’Ivoire, the results in this article suggest that as of the 1930s, French colonial policymakers recognised their threat, while the British failed to do so sufficiently. A second new dataset of colonial vaccination campaigns (for ca. 1900–1955) formed the basis of an analysis of this aspect of the colonial response outside health care facilities. It finds that several diseases (including yellow fever) were addressed – more so in Côte d’Ivoire than in Ghana – but that smallpox vaccination campaigns trumped all others. The findings of this analysis indicate that extensive smallpox campaigns occurred earlier in both countries than previously suggested by the literature, and that the French colonial administration imposed a more elaborate programme.